2014
DOI: 10.1038/bmt.2014.207
|View full text |Cite
|
Sign up to set email alerts
|

Is ‘informed consent’ an ‘understood consent’ in hematopoietic cell transplantation?

Abstract: Hematopoietic cell transplantation (HCT) is a complex and highly specialized medical treatment that is associated with significant risks, including death. Furthermore, transplantation is offered to patients who often have no other curative treatment alternatives. The routine-consent process for HCT typically occurs before HCT and is influenced by many factors related to patients, physicians and the transplant per se. These factors can impede the consent process and subsequently result in a failure of proper en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 30 publications
0
46
0
1
Order By: Relevance
“…How can an HCT team help maximize their patient's ability to make an informed choice? In a thorough discussion, D'Souza et al 12 captured many pitfalls in the current HCT informed consent process and concluded that new avenues should be sought to help patients make an informed decision. They suggested opportunities for improvement including the use of interactive technology, consideration about what information is actually meaningful for the patient's decision and enhancement of the consent forms.…”
Section: Older Patients With Other Diseases: Decision Making In Nephrmentioning
confidence: 99%
See 4 more Smart Citations
“…How can an HCT team help maximize their patient's ability to make an informed choice? In a thorough discussion, D'Souza et al 12 captured many pitfalls in the current HCT informed consent process and concluded that new avenues should be sought to help patients make an informed decision. They suggested opportunities for improvement including the use of interactive technology, consideration about what information is actually meaningful for the patient's decision and enhancement of the consent forms.…”
Section: Older Patients With Other Diseases: Decision Making In Nephrmentioning
confidence: 99%
“…12 They see the decision as either choosing life (transplant) or choosing death (no transplant). From diagnosis onward, health-care professionals may subtly or not so subtly give the message that the goal is the potentially curative option of transplant.…”
Section: Differences In Decision Considerations Between Younger and Omentioning
confidence: 99%
See 3 more Smart Citations